Mortality profile of neurological diseases in Brazil’s Northeast region (Research, Society and Development, 2025)
Neurological diseases represent a substantial impact on public health systems worldwide, especially in low- and middle-income regions, where structural inequalities limit access to specialized care. Therefore, this study aimed to analyze the mortality profile from nervous system diseases in the Northeast region of Brazil between 2000 and 2022, using data from the SIM/DATASUS system, contributing to the development of prevention strategies, the organization of the care network, and the reduction of health inequities. A total of 128,411 deaths were identified, with Bahia, Ceará, and Pernambuco presenting the highest proportions. Mortality occurred predominantly among men, individuals of mixed race, and people without formal education. Alzheimer's disease, epilepsy, and cerebral palsy emerged as the main causes in different age groups. The results point to the need to strengthen epidemiological surveillance, improve health information systems, and implement neurological care policies aimed at reducing regional inequalities.